Morphological and Biochemical Properties of Four Members of a Novel Group of Reoviruses Isolated from Aquatic Animals - Winton, J. R.; Lannan, C. N.; Fryer, J. L.; Hedrick, R. P.; Meyers, T. R.; Plumb, J. A.; Yamamoto, T. (Journal of General Virology, 1987)
SUMMARY The morphological, biochemical and growth characteristics of four members of the Reoviridae, three from the fish hosts, golden shiner (Notemigonus crysoleucas), chum salmon (Oncorhynchus keta) and channel catfish (Ictalurus punctatus) and one from American oyster (Crassostrea virginica), were compared. Electron microscopy of negatively stained virions revealed icosahedral particles approximately 75 nm in diameter composed of a double capsid. Complete particles had buoyant densities in CsCl of 1·34 to 1·36 g/ml. The viruses replicated well in several fish cell lines, forming plaque-like syncytia in monolayer cultures. Each virus could be distinguished by the range of cell lines supporting its growth. Polyacrylamide gel electrophoresis showed that the genome of each virus was composed of 11 segments of dsRNA distributed among three size classes. There were three large, three medium and five small segments in each genome and each isolate had a unique electropherotype. The segments ranged from 2·5 × 106 to 0·31 × 106 mol. wt. with a total genome of approximately 15 × 106 mol. wt. Analysis by SDS-PAGE revealed that each virus had five major structural proteins. There were two large polypeptides of approximately 135000 and 125000 mol. wt., one medium size polypeptide of 70000 mol. wt. and two small polypeptides of 45000 and 34000 mol. wt. Of the major structural proteins, those of approximately 70000 and 34000 mol. wt. were consistently present in the highest concentrations. Minor virion proteins were detected but were not characterized. These four viruses, isolated from aquatic animals, were unlike viruses of the six established genera of the Reoviridae.
Keywords: fish